Latrophilin receptors: novel bronchodilator targets in asthma. Issue 1 (20th June 2016) - Faiz, A; Donovan, C; Nieuwenhuis, M AE; van den Berge, M; Postma, D S; Yao, S; Park, C Y; Hirsch, R; Fredberg, J J; Tjin, G; Halayko, A J; Rempel, K L; et al.
Abstract : Background: Asthma affects 300 million people worldwide. In asthma, the major cause of morbidity and mortality is acute airway narrowing, due to airway smooth muscle (ASM) hypercontraction, associated with airway remodelling. However, little is known about the transcriptional differences between healthy and asthmatic ASM cells. Objectives: To investigate the transcriptional differences between asthmatic and healthy airway smooth muscle cells (ASMC) in culture and investigate the identified targets using in vitro and ex vivo techniques. Methods: Human asthmatic and healthy ASMC grown in culture were run on Affymetrix_Hugene_1.0_ST microarrays. Identified candidates were confirmed by PCR, and immunohistochemistry. Functional analysis was conducted using in vitro ASMC proliferation, attachment and contraction assays and ex vivo contraction of mouse airways. Results: We suggest a novel role for latrophilin (LPHN) receptors, finding increased expression on ASMC from asthmatics, compared with non-asthmatics in vivo and in vitro, suggesting a role in mediating airway function. A single nucleotide polymorphism in LPHN1 was associated with asthma and with increased LPHN1 expression in lung tissue. When activated, LPHNs regulated ASMC adhesion and proliferation in vitro, and promoted contraction of mouse airways and ASMC. Conclusions: Given the need for novel inhibitors of airway remodelling and bronchodilators in asthma, the LPHN family may represent promising novel targets for future dual therapeutic intervention.